Changes in Microstructure, Germination, Sprout Growth, Phytochemical and Microbial Quality of Ultrasonication Treated Adzuki Bean Seeds - Kai-Ying Chiu (Agronomy, 2021)
Sprout is a nutritious ready-to-eat vegetable. In this study, we examined the effects of ultrasonication treatments (treated with 28, 40 or 80 kHz frequency for 10 min at 25 °C) on the changes in microstructure, seed hydration and germination, sprout growth, sprout quality, and microbial load of two adzuki bean (Vigna angularis) varieties (Kaohsiung 8 and Kaohsiung 10). The results indicated that the ultrasonication at 40 kHz or 80 kHz improved seed hydration and enhanced germination; this is linked to the ultrasound-induced microstructure changes in the hilum and seed coat surface of treated seeds. The ultrasonication-increased sprout growth and yield were possibly attributable to the increased α-amylase activity during germination. Ultrasonication also improved total polyphenols, total flavonoids, and total saponins contents and further enhanced the anti-oxidative activities (FRAP and DPPH) of produce sprouts. The results further indicated that the 40 kHz or 80 kHz treatment decreased microbial loads of treated sprouts to an acceptable level; therefore, these two treatments can be used for germination improvement and an effective microbial control treatment for adzuki bean sprout production.